Elaboración y utilización de audiovisuales en la enseñanza de la química - Llitjós Viza, Anna; Estopà Miró, C.; Miró Clària, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This article shows the process of elaboration, and the optimal conditions for their use, of audiovisuals as backup material for chemistry classes. We distinguish between producing videos for internal and external use. We stress the importance of the technical quality and the content of videos for external use, and the importance of the teamwork involved in their preparation too. We also examine the role of the scientist at each stage of the process of producing audiovisuals. Finally, we presenta series of videos that we have made, and suggest possible lines of research for future projects in this field.